Analysis of predictor factors of limb amputation in patients with high-voltage electrical burns - García Álvarez, Guillermo (2015)
Objective: Limb amputation is considered one of the most devastating consequences of electrical injury. Any factors that correlate with the degree of muscle damage can be used to predict the necessity of limb amputation. The aim of this study was to determine the factors that can be used to predict limb amputation in high-voltage electrically injured patients. Material and Methods: Ninety-seven high-voltage electrically injured patients were admitted to the Department of Plastic and Reconstructive Surgery and Burns of Hospital Nacional Arzobispo Loayza on a 5 year period. A retrospective analysis of the possible related risk factors between amputation and on-amputation patients was performed. Results: A total of 64 patients were enrolled for analysis. Fifteen patients underwent limb amputations. Multivariate analysis of the risk factors between amputation and non-amputation groups showed statistical significance for first 24 hour creatine kinase-isoenzyme MB (CKMB) level. A serum CK-MB level above 14,955 U/L predicted high risk of limb amputation with high specificity (83%) and sensitivity (76%). Only one patient with a remarkable decrease of creatine kinase (CPKt) and CK-MB levels after fasciotomy avoided a major limb amputation. Conclusions: Our results suggest that CPK-MB level is an independent factor for prediction of limb amputation in patients with high-voltage electrical burns. We suggest that the addition of CPK-MB evaluation to clinical symptom screening may be avaluable method for early detection of muscle damage.